Pentingnya Pendidikan Character Building dalam Membentuk Kepribadian Mahasiswa - Tanis, Hibur (Bina Nusantara University, 2013)
Character education at various universities in Indonesia have been getting attention even has become a priority. However, the extent to which this character education can be designed as an integral part of formal education. This paper discusses the importance of teaching Character building as part of character education in the formal education system in the course of Bina Nusantara University of Character Building. Character Education Building is arranged in a systematic and integrated in the Curriculum Lecture of CBDC. Therefore, one said education act is always active and planned, then education is a conscious act or action in order to change attitudes and code of conduct that is expected humanizing intelligent, skilled, independent, disciplined, and noble. However in the application, design and implementation of the program courses Character building is kept under review by the team as part of efforts for continuous improvement.